1993
DOI: 10.2307/4088649
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Black Bib of the Eurasian Siskin (Carduelis spinus) and Its Role as a Reliable Badge of Dominance

Abstract: Rohwer (1975, 1982) proposed that the variation and extent of color patches in the plumage of wintering birds could work as badges of social status. The major advantage of these signals would be that individuals of unequal status competing for limited resources would not need to risk accidental injury or waste energy assessing the relative fighting ability of potential opponents (Rohwer 1982). The status-signalling hypothesis has been tested in several species with variable plumage (reviewed by Whitfield 1987;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…In this study, we found no differences between male resident and transient wintering siskins in the black bib area, which is the best proxy for RHP in male siskins (Senar et al 1993;Senar and Camerino 1998). The black bib area alone explained about half of the variation in dominance score (i.e.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In this study, we found no differences between male resident and transient wintering siskins in the black bib area, which is the best proxy for RHP in male siskins (Senar et al 1993;Senar and Camerino 1998). The black bib area alone explained about half of the variation in dominance score (i.e.…”
Section: Discussionmentioning
confidence: 63%
“…Variation in the relative importance of predation and starvation risks has been proposed to explain these differences, both between and within species (Verhulst and Hogstad 1996). The black bib area of male siskins is positively associated to exploratory behaviour (Mateos-González and Senar 2012) and competitive ability (Senar et al 1993;Senar and Camerino 1998) and, hence, to the personality of birds (Réale et al 2007). Since residency is not related to the black bib size, it is probably not either related to personality, and hence, the dominance of residents over transients is not expected to result from a behavioural syndrome but from a difference in prior residency.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These traits may function in a social context, as most siskin species gather in large numbers outside the breeding season, also forming mixed flocks that consist of different species. Senar and colleagues [33,34] showed in experiments that enlargements or removals of black bibs in the European siskin C. spinus, (a species resembling the ancestral C. barbata in this trait) have an effect on social status. Large bibs in spinus signalled overt aggression and thus dominant status.…”
Section: ) Phenetic Charactersmentioning
confidence: 99%